2016
DOI: 10.1038/oncsis.2016.29
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of YAP-dependent Nupr1 promotes tumor-repopulating cell growth in soft matrices

Abstract: Despite decades of significant progress in understanding the molecular mechanisms of malignant tumorigenic cells, it remains elusive what these tumorigenic cells are and what controls the growth of these malignant cells. Recently, we have mechanically selected and grown highly malignant and tumorigenic tumor-repopulating cells (TRCs), a small sub-population of cancer cells, by culturing single cancer cells in soft fibrin matrices. However, it is unclear what regulates TRC growth besides Sox2. Here we show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 27 publications
1
27
0
Order By: Relevance
“…It would be difficult to interpret this force-induced rapid transcription of DHFR by models of diffusion or translocation of FA proteins or other cytoplasmic molecules such as Yes-associated Protein (YAP)/transcriptional coactivator with PDZ-binding motif (TAZ) [74] or TWIST1 [75] into the nucleus, which can certainly regulate matrix rigidity/force dependent gene expression at longer time scales (~tens of minutes). Matrix force dependent cytoplasmic YAP translocation into the nucleus is indeed necessary for gene upregulation of nuclear protein 1 (Nupr1), whose role as a tumor suppressor is just recently discovered [76]. Histone modifications in the nucleus are one of the major means of epigenetic alterations to regulate gene expression.…”
Section: Nuclear Mechanotransductionmentioning
confidence: 99%
“…It would be difficult to interpret this force-induced rapid transcription of DHFR by models of diffusion or translocation of FA proteins or other cytoplasmic molecules such as Yes-associated Protein (YAP)/transcriptional coactivator with PDZ-binding motif (TAZ) [74] or TWIST1 [75] into the nucleus, which can certainly regulate matrix rigidity/force dependent gene expression at longer time scales (~tens of minutes). Matrix force dependent cytoplasmic YAP translocation into the nucleus is indeed necessary for gene upregulation of nuclear protein 1 (Nupr1), whose role as a tumor suppressor is just recently discovered [76]. Histone modifications in the nucleus are one of the major means of epigenetic alterations to regulate gene expression.…”
Section: Nuclear Mechanotransductionmentioning
confidence: 99%
“…Activates p53 in response to mitotic stress 53,[142][143][144]149 Activates p53 in response to oncogenic Ras 117,118 Activates p53 in response to excess cholesterol 156 Activates p53 during mESC differentiation 52 YAP Loss of YAP induces p53 145,147,148 YAP represses ΔNp63 to inhibit lung cancer squamous cells transdifferentiation. 182 YAP-p73 promotes apoptosis 106,108-110, 132-134, 136,183 Yki inactivation induces Dmp53 119 p63 inhibits p73-YAPdependent apoptosis 22,137 YAP-tyr357-p73 is a marker for well differentiated HCC 85 Yki binds Dmp53 to promote apoptosis 131 YAP positively regulates p63 in epidermal stem cells 66 Locus is amplified in p53 null tumors [75][76][77]184,185 YAP positively regulates p63 in airway epithelium 71 p53 and YAP antagonistically regulate FOXM1 [186][187][188] YAP-p63 block differentiation in HNSCC 86 p53 transactivates 14-3-3σ, which inhibits YAP/TAZ 124,125 Binds p63 and prevents its degradation 88,89 YAP and p53 cooperate in apoptosis and senescence [126][127][128] Hyperactivation of YAP/TAZ induces p53 152,154 YAP and mutp53 cooperate in transformation 33,82 Mutp53 induces miRs that tar...…”
Section: Lats2mentioning
confidence: 99%
“…In highly malignant tumorrepopulating cells, which are enriched by growing cancer cells on a soft matrix, the expression of nuclear protein 1 (NURP1) is compromised by reduced nuclear localization of YAP. 126 Reduction in NURP1 expression is followed by a reduction in p53 mRNA and protein levels, suggesting an antitumorigenic axis involving YAP-NUPR1-p53. Similarly, YAP increases the sensitivity of hepatocellular and renal carcinoma cells to chemotherapy by increasing p53 expression and activity.…”
Section: Regulation Of Apoptosismentioning
confidence: 99%
“…Silencing of NUPR1 in pancreatic or hepatocellular cancer cells decreases migration and invasion, presumably through its target genes, ATF4 (activating transcription factor 4), DDIT3/CHOP (DNA damage inducible transcript 3) and TRIB3 (tribbles pseudokinase 3), acting via endoplasmic reticulum (ER) stress activation [12][13][14]. Conversely, NUPR1 also acts as a putative tumor suppressor in prostate cancer, ovarian cancer and synovial sarcoma [15][16][17]. Recent studies have also demonstrated that this multifunctional protein influences cell fate determination, which implicates it as a potential therapeutic target [18,19] Although substantial information exists regarding NUPR1 in the setting of gene regulation, the role of NUPR1 in the autolysosomal process is uncharacterized.…”
Section: Introductionmentioning
confidence: 99%